Chronic kidney disease progression and mortality risk profiles in Germany: results from the Chronic Kidney Disease Outcomes and Practice Patterns Study. Issue 5 (18th January 2020) - Reichel, Helmut; Zee, Jarcy; Tu, Charlotte; Young, Eric; Pisoni, Ronald L; Stengel, Bénédicte; Duttlinger, Johannes; Lonnemann, Gerhard; Robinson, Bruce M; Pecoits-Filho, Roberto; Fliser, Danilo
Abstract: Background: Chronic kidney disease (CKD) progression among German patients in a representative setting has not been described previously. The Verband Deutsche Nierenzentren and Chronic Kidney Disease Outcomes and Practice Patterns Study established a longitudinal observational cohort among German CKD patients to research variations in patient care and outcomes in real-world nephrology practices. Methods: A cohort of CKD Stages 3 (25%) and 4 (75%) patients was established from German nephrologist-run CKD clinics in 2013–16. Linear models were used to determine the estimated glomerular filtration rate (eGFR) slope during follow-up and Cox models were used to assess outcomes of end-stage kidney disease (ESKD) and death. Results: A total of 1834 patients (median age 75 years, 58% male, 42% diabetics, median baseline eGFR 25 mL/min/1.73 m 2 ) were followed for a median of 29 months. More than 50% had slow or no decline and 17% declined ≥5 mL/min/1.73 m 2 /year. After 4.5 years, the incidence of ESKD was 8% and of deaths without ESKD 16% among patients with eGFR ≥30 mL/min/1.73 m 2 and 37% and 19% for eGFR <30 mL/min/1.73 m 2 . Adjusted models showed higher risks of ESKD or death for patients with worse kidney function at baseline, male sex, diabetes and higher blood pressure; a higher risk of ESKD with higher albuminuria; and a higher risk of death with older age or cardiovascular comorbidity. Conclusions: Routine nephrology care of patients in Germany comprises mostly elderly patients, many with slow CKD progression. Identification of risk factors for CKD progression and mortality may help guide resources by closer follow-up of high-risk patients.